TEYL: Fun Speaking with Foreign Teachers - Indah Werdiningsih (Universitas Ahmad Dahlan, 2022)
In regard to the current innovation on multi-dimensional learning systems in industrial era 4.0, teachers and educators worldwide strive for students to have a strong foundation in mastering English, one of which is speaking skills. Teachers help students build self-confidence and provide innovative technology that enables them to practice and focus on their own unique needs outside the classroom. There are alternatives to bring these goals into reality: first is to create a positive, fun learning environment both at school and at home. Second, to provide new experiences for students to directly interact with foreigners who teach and use English as their first language. This research investigatesstudents’ speaking skills in the lower-class group of elementary school (28 second graders, aged seven to eight years old). The study also thoroughly explored how foreign teachers’ fun activities during classroom hours can affect students’ speaking. In order to find answers to the research problems, simple conversation to test the speaking ability was conducted. After the test, the teacher helped students fill out a questionnaire to know their perception of learning with foreign teachers and their opinion on doing interactive games and outdoor activities during classroom-hour. The speaking ability of the second graders in SD Negeri Jember Lor 3 is sufficient, and they can pronounce some vocabularies correctly and conduct simple conversations with foreigners. The adequate mastery of the conversation may be following the pattern of various determinants, especially factors concerning the help from foreign teachers who model pronunciation, sentence stress, grammar, intonation, and vocabulary in a valid and veritable accent.